CORSmonit: GNSS networks remote monitoring system - Venâncio, Pedro Miguel Henriques (2015)
The task of monitoring a GNSS (Global Navigation Satellite Systems) network requires time, human resources and a need for automation, which increases proportionally with the number of stations included in the network. The solutions that are actually avaiable in the market have high comercial value and in most of the times this makes it unavailable for an organization. This thesis presents a real time GNSS networks monitoring system that signi cantly reduces the time and e ort needed to execute this task. Furthermore, an useful front-end, for publication of related network monitoring information, was developed and implemented.